Phase 1b/2a study of trastuzumab emtansine (T-DM1), paclitaxel, and pertuzumab in HER2-positive metastatic breast cancer. Issue 1 (December 2016) - Krop, Ian; Modi, Shanu; LoRusso, Patricia; Pegram, Mark; Guardino, Ellie; Althaus, Betsy; Lu, Dan; Strasak, Alexander; Elias, Anthony
Abstract Background In pre-clinical studies, the anti-tumor activity of T-DM1 was enhanced when combined with taxanes or pertuzumab. This phase 1b/2a study evaluated the safety/tolerability of T-DM1 + paclitaxel ± pertuzumab in HER2-positive advanced breast cancer. Methods In phase 1b (n = 60), a 3 + 3 dose-escalation approach was used to determine the maximum tolerated dose (MTD) of T-DM1 + paclitaxel ± pertuzumab. The primary objective of phase 2a was feasibility, with 44 patients randomized to T-DM1 + paclitaxel ± pertuzumab at the MTD identified in phase 1b. Results The MTD was T-DM1 3.6 mg/kg every three weeks (q3w) or 2.4 mg/kg weekly + paclitaxel 80 mg/m2 weekly ± pertuzumab 840 mg loading dose followed by 420 mg q3w. Phase 2a patients had received a median of 5.0 (range: 0–10) prior therapies for advanced cancer. In phase 2a, 51.2 % received ≥12 paclitaxel doses within 15 weeks, and 14.0 % received 12 paclitaxel doses by week 12. Common all-grade adverse events (AEs) were peripheral neuropathy (90.9 %) and fatigue (79.5 %). A total of 77.3 % experienced grade ≥3 AEs, most commonly neutropenia (25.0 %) and peripheral neuropathy (18.2 %). Among the 42 phase 2a patients with measurable disease, the objective response rate (ORR) was 50.0 % (95 % confidence interval (CI) 34.6–65.4); the clinical benefit rate (CBR) was 56.8 % (95 % CI 41.6–71.0). No pharmacokinetic interactions were observed between T-DM1 and paclitaxel. Conclusions This regimen showed clinical activity. Although there is potential for paclitaxel to be added to T-DM1 ± pertuzumab, peripheral neuropathy was common in this heavily pretreated population. Trial registration ClinicalTrials.govNCT00951665 . Registered August 3, 2009.